UJI DAYA HAMBAT PERMEN JELI LIDAH BUAYA TERHADAP Streptococcus mutans - Chairani, Shanty (Jurnal Kesehatan Gigi dan Mulut (JKGM), 2023)
Background: The bacteria which has an important role in the dental cariess process is Streptococcus mutans. Antibacterial agent which can inhibit or kill Streptococcus mutans there was aloe vera that can be made as a product like jelly candy. The aim of this study was to determined antibacterial activity of aloe vera jelly candy on the growth of Streptococcus mutans. Methods: An in vitro experimental laboratory used in this study. Well diffusion method was used to determined antibacterial activity of Streptococcus mutans and there were two sample groups: aloe vera jelly candy and jelly candy without aloe vera. Antibactrial activity of jelly candy was measured by calculated zone of inhibiton in milimeter using caliper. Independent T-test was used to analyzed the mean zone of inhibiton and assess the difference in significance between the test groups. Results: Aloe vera jelly candy could inhibit Streptococcus mutans significantly compared to jelly candy without aloe vera (p<0,05). Conclusion: Aloe vera jelly candy had the potential to be used for prevention of dental caries because it had antibacterial activity against Streptococcus mutans.